Sociocultural Elite and Social Conflict in Contemporary Civilization (Projections on Arab society in light of the identity crisis) - أسعد, سامر; عــادل ديــاب الـعـلي, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research paper discusses culture in modern society and its challenges, highlighting the challenges of cultural globalization and its impact on cultural identities. It suggests that contemporary vision disapproves of traditional ideas of authority, expertise, and objectivity, and focuses on deconstructing reality and self-experience. Some individuals believe that the traditional role of the intellectual has become outdated in the postmodern era and that intellectuals should strive to avoid isolation from the public and enhance communication and exchange with them. This research emphasizes the importance of integrating concepts of diversity, pluralism, and self-experience in the works of intellectuals to stay connected with the spirit of the times. It stresses the preservation of intellectual freedom and their role in shaping public opinion, without being constrained by limitations that hinder their role and contribution. Generally, the research addresses the topic of public opinion and the mutual influence between intellectuals and the public, as well as the role of media in shaping public opinion. It underscores the significance of genuine communication and exchange of ideas to achieve more accurate and comprehensive visions, promote societal development, and bring about social change